The Effectiveness of Using the Question-and-Answer Method to Increase Student Activeness in Indonesian Language Learning at Elementary School of Nurul Hidayah, Pamulang, South Tangerang - Sarah Hanan Sahara; Afifuddin Ahmad Robbani; M. Agus Nurahman (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2026)
This study aimed to determine the effectiveness of the question-and-answer method in improving students’ activeness and learning outcomes in Indonesian language subjects. The research method used was Classroom Action Research (CAR), which was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects were 22 second-grade students. Data collection techniques included observation, interviews, tests, and documentation. The results showed that the implementation of the question-and-answer method was able to improve students’ activenessand learning outcomes. In the pre-cycle stage, the percentage of students achieving learning mastery was only 40.9%, which increased to 68.2% in Cycle I and further increased to 95.5% in Cycle II. In addition, students became more active in asking and answering questions, participating in discussions, and expressing opinions during the learning process. Therefore, it can be concluded that the question-and-answer method is effective in improving students’ activeness and learning outcomes in Indonesian language learning at the elementary school level.